A review of randomised controlled trials comparing ultrasound-guided foam sclerotherapy with endothermal ablation for the treatment of great saphenous varicose veins. (May 2016) - Davies, Huw OB; Popplewell, Matthew; Darvall, Katy; Bate, Gareth; Bradbury, Andrew W
Objective: The last 10 years have seen the introduction into everyday clinical practice of a wide range of novel non-surgical treatments for varicose veins. In July 2013, the UK National Institute for Health and Care Excellence recommended the following treatment hierarchy for varicose veins: endothermal ablation, ultrasound-guided foam sclerotherapy, surgery and compression hosiery. The aim of this paper is to review the randomised controlled trials that have compared endothermal ablation and ultrasound-guided foam sclerotherapy to determine if the level 1 evidence base still supports an "endothermal ablation first" strategy for the treatment of varicose veins. Methods: A PubMed and OVID literature search (until 31 January 2015) was performed and randomised controlled trials comparing endothermal ablation and ultrasound-guided foam sclerotherapy were obtained. Results: Although anatomical success appeared higher with endothermal ablation than ultrasound-guided foam sclerotherapy, clinical success and patient-reported outcomes measures were similar. Morbidity and complication rates were very low and not significantly different between endothermal ablation and ultrasound-guided foam sclerotherapy. Ultrasound-guided foam sclerotherapy was consistently less expensive that endothermal ablation. Conclusions: All endovenous modalities appear to be successful and have a role in modern day practice. Although further work is required to optimise ultrasound-guided foam sclerotherapy technique to maximise anatomical success and minimise retreatment, the present level 1 evidence base shows there is no significant difference in clinical important outcomes between ultrasound-guided foam sclerotherapy and endothermal ablation. As ultrasound-guided foam sclerotherapy is less expensive, it is likely to be a more cost-effective option in most patients in most healthcare settings. Strict adherence to the treatment hierarchy recommended by National Institute for Health and Care Excellence seems unjustified.